Anthropometrical characteristics of the population of the Island of Rab - Pribačić Ambrožić, Vanda (Array, 2009)
Abstract: The paper presents the results of the population structure research on the inhabitants of the Island of Rab by the analysis of anthropometric, continuous characteristics (morphological variables of head and body) on the representative sample of 601 adult persons (aged 18–75 years) from the settlements Banjol, Barbat, Lopar, Rab and Supetarska Draga (Figure 1). The aim was to investigate the possibility to confirm the existence of population groupings or divisions in one geographically limited area based on the analysis of continuous anthropometric variables. In other words, the purpose is to investigate the structure of the inhabitants in order to contribute to the explanation of its microevolution. The performed analysis shows partial anthropometric variability of the present day population that is confirmed by a series of biostatistics analyses. The analysis includes continuous (quantitative) characteristics, 36 anthropometric body variables and 14 anthropometric head variables. Heterogeneity among the groups of examinees is evaluated for separate phenotypic characteristics in order to obtain the data on the inhabitants’ microevolution. The estimation performed on the total of 36 analyzed body variables showed the existence of statistically significant heterogeneities for 13 variables in men and for women in 8. By descriptive statistic procedures and by the estimation of heterogeneity, in space of the head related phenotypic characteristics, heterogeneity was found for 7 characteristics in men and for 5 in women. Discrimination analyses show that certain heterogeneity exists in some investigated continuous characteristics among individual populations. The results of the biological distances evaluation among the populations of the Island of Rab point to the separation of some populations, primarily of the inhabitants of Lopar